Lack of IL-1R8 in neurons causes hyperactivation of IL-1 receptor pathway and induces MECP2-dependent synaptic defects - Tomasoni, Romana (eLife, 2017)
Inflammation modifies risk and/or severity of a variety of brain diseases through still elusive molecular mechanisms. Here we show that hyperactivation of the interleukin 1 pathway, through either ablation of the interleukin 1 receptor 8 (IL-1R8, also known as SIGIRR or Tir8) or activation of IL-1R, leads to up-regulation of the mTOR pathway and increased levels of the epigenetic regulator MeCP2, bringing to disruption of dendritic spine morphology, synaptic plasticity and plasticity-related gene expression. Genetic correction of MeCP2 levels in IL-1R8 KO neurons rescues the synaptic defects. Pharmacological inhibition of IL-1R activation by Anakinra corrects transcriptional changes, restores MeCP2 levels and spine plasticity and ameliorates cognitive defects in IL-1R8 KO mice. By linking for the first time neuronal MeCP2, a key player in brain development, to immune activation and demonstrating that synaptic defects can be pharmacologically reversed, these data open the possibility for novel treatments of neurological diseases through the immune system modulation. DOI: http://dx.doi.org/10.7554/eLife.21735.001